Monitoring Collagen Synthesis in Fibroblasts Using Fluorescently Labeled tRNA Pairs. Issue 9 (September 2014) - Liu, Jiaqi; Pampillo, Macarena; Guo, Fen; Liu, Shangxi; Cooperman, Barry S.; Farrell, Ian; Dahary, Dvir; Gan, Bing S.; O'Gorman, David B.; Smilansky, Zeev; Babwah, Andy V.; Leask, Andrew
<x xml:space="preserve">Abstract</x> There is a critical need for techniques that directly monitor protein synthesis within cells isolated from normal and diseased tissue. Fibrotic disease, for which there is no drug treatment, is characterized by the overexpression of collagens. Here, we use a bioinformatics approach to identify a pair of glycine and proline isoacceptor tRNAs as being specific for the decoding of collagen mRNAs, leading to development of a FRET‐based approach, dicodon monitoring of protein synthesis (DiCoMPS), that directly monitors the synthesis of collagen. DiCoMPS aimed at detecting collagen synthesis will be helpful in identifying novel anti‐fibrotic compounds in cells derived from patients with fibrosis of any etiology, and, suitably adapted, should be widely applicable in monitoring the synthesis of other proteins in cells. J. Cell. Physiol. 229: 1121–1129, 2014. © 2014 Wiley Periodicals, Inc.